Reductive modification of genetically encoded 3-nitrotyrosine sites in alpha synuclein expressed in E.coli - Gerding, Hanne R. (Redox Biol, 2019)
Tyrosine nitration is a post-translational protein modification relevant to various pathophysiological processes. Chemical nitration procedures have been used to generate and study nitrated proteins, but these methods regularly lead to modifications at other amino acid residues. A novel strategy employs a genetic code modification that allows incorporation of 3-nitrotyrosine (3-NT) during ribosomal protein synthesis to generate a recombinant protein with defined 3-NT-sites, in the absence of other post-translational modifications. This approach was applied to study the generation and stability of the 3-NT moiety in recombinant proteins produced in E.coli. Nitrated alpha-synuclein (ASYN) was selected as exemplary protein, relevant in Parkinson's disease (PD). A procedure was established to obtain pure tyrosine-modified ASYN in mg amounts. However, a rapid (t(1/2) = 0.4 h) reduction of 3-NT to 3-aminotyrosine (3-AT) was observed. When screening for potential mechanisms, we found that 3-NT can be reduced enzymatically to 3-AT, whilst biologically relevant low molecular weight reductants, such as NADPH or GSH, did not affect 3-NT. A genetic screen for E.coli proteins, involved in the observed 3-NT reduction, revealed the contribution of several, possibly redundant pathways. Green fluorescent protein was studied as an alternative model protein. These data confirm 3-NT reduction as a broadly-relevant pathway in E.coli. In conclusion, incorporation of 3-NT as a genetically-encoded non-natural amino acid allows for generation of recombinant proteins with specific nitration sites. The potential reduction of the 3-NT moiety by E.coli, however, requires attention to the design of the purification strategy for obtaining pure nitrated protein.